2022
DOI: 10.1200/go.21.00424
|View full text |Cite
|
Sign up to set email alerts
|

Forty-Five Years of Research and Progress in Breast Cancer: Progress for Some, Disparities for Most

Abstract: Gains in Breast Cancer Treatment Unavailable for MostAuthor affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the case of breast cancer, there is widespread evidence of insufficient decision-making that is not based on best medical practice standards and inappropriate treatment and follow-up by providers and patients [ 23 ]. The surgical treatments for breast cancer have changed dramatically, from radical mastectomy to breast-conserving surgery [ 83 ]. About one-third of women with breast cancer in Kosovo still have a mastectomy [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of breast cancer, there is widespread evidence of insufficient decision-making that is not based on best medical practice standards and inappropriate treatment and follow-up by providers and patients [ 23 ]. The surgical treatments for breast cancer have changed dramatically, from radical mastectomy to breast-conserving surgery [ 83 ]. About one-third of women with breast cancer in Kosovo still have a mastectomy [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…It confirms many publicly known facts about the management of NCDs that are valid for most of the healthcare provided in the country. For example, studies have reported that the system is underfunded, [ 4 , 11 , 87 ] care availability is limited in quality and quantity, [ 4 , 83 ] issues exist relating to availability and impact of the application of clinical standards [ 4 , 15 , 84 ], and there are issues with supply with the workforce [ 11 , 88 ]. This review highlights the issues with a defragmented system of provision of NCD care, as well as efforts in the function of improvement of the existing situation.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer‐related cognitive impairment (CRCI) is an increasing issue in cancer survivors, especially in older survivors 1 . Recent advancements in cancer treatment, such as targeted therapies, immunotherapy, and endocrine therapy, have improved breast cancer survival 2,3 . CRCI has been reported in cancer survivors, which affects their quality of life 4 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Recent advancements in cancer treatment, such as targeted therapies, immunotherapy, and endocrine therapy, have improved breast cancer survival. 2 , 3 CRCI has been reported in cancer survivors, which affects their quality of life. 4 Older survivors may have persistent CRCI, particularly in attention, processing speed, working memory, and executive function, even several years after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts to promote early diagnosis are still a primary focus of fighting breast cancer. Early diagnosis is associated with reduced mortality, and long intervals between breast cancer detection and treatment initiation can impact the prognosis of the disease (Hoxha et al, 2022). Therefore, it is essential to minimize delays in disease detection and diagnosis.…”
Section: Introductionmentioning
confidence: 99%